Unveiling the Costs of Inaction and Benefits of Actions to Control Land Degradation - Yigezu, Yigezu (International Center for Agricultural Research in the Dry Areas, 2024)
ICARDA’s innovative Analysis Pack for Economics of Land Degradation (APELD) tool, developed through the CGIAR Research Initiative on Livestock and Climate, quantifies economic losses of Land degradation (LD) and analyzes the benefits of land rehabilitation interventions.